Low-waviness galvanized IF steel outer plate and preparation method thereof

By optimizing the entire process of the steel plate, including controlling chemical composition and process parameters, and preparing low-corrugation galvanized IF steel outer plate, the problem of excessive corrugation of the steel plate after stamping deformation is solved, and the reduction of the corrugation after forming and the improvement of the coating quality is achieved.

CN119506705APending Publication Date: 2025-02-25МААНЬШАНЬ АЙРОН ЭНД СТИЛ КО ЛТД
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411621978.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

In the prior art, due to the excessive corrugation of the steel plate after stamping deformation, the long-wave exceeds the standard caused by the 2C1B coating process using the 2C1B coating process without intermediate coating, and the corrugation after forming does not meet the standard requirements.

Method used

By optimizing the entire process, controlling chemical composition and process parameters, including appropriate final rolling temperature, coiling temperature, hot-dip galvanized conditions and light-finished rolling force, low-wavelength galvanized IF steel outer plate is prepared. Specific steps include hot rolling, cold rolling, continuous annealing, hot dip galvanizing and polishing.

Benefits of technology

It significantly improves the brightness of the coating after steel plate forming, reduces the corrugation, meets the standard requirements of the intermediate-free coating process, and improves the production efficiency of car companies.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119506705A_ABST
    Figure CN119506705A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of steel rolling, and discloses a low-waviness galvanized IF steel outer plate and a preparation method thereof.The low-waviness galvanized IF steel outer plate comprises, by weight, 0 < C < = 0.0035%, 0 < Si < = 0.03%, 0.08% < = Mn < = 0.25%, 0 < P < = 0.02%, 0 < S < = 0.015%, 0.02% < = Al < = 0.055%, 0.02% < = Ti < = 0.075%, 0 < = Nb < = 0.035%, 0 < = N < = 0.005% and the balance Fe and inevitable impurities; and the waviness Wsa of the low-waviness galvanized IF steel outer plate is less than or equal to 0.35 mu m. According to the scheme, the problem that long waves generated by a floating-coat-free 2C1B coating process exceed the standard due to the fact that the corrugation degree is too high after the steel plate is subjected to stamping deformation is solved, the brightness of the steel plate after forming and coating can be greatly improved, and the method has important significance on improving the production efficiency of turning enterprises.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of steel rolling, and in particular to a low-corrugation galvanized IF steel outer plate and a preparation method thereof. Background Art

[0002] Galvanized IF steel automotive outer panels mainly refer to low-carbon products of DDQ, EDDQ, SEDDQ and other grades, and are mainly used in front and rear door panels, fenders, side panels and other parts of automobiles. Parts with different uses have different requirements for product surface quality and formability, and the main engine manufacturers are also gradually promoting the coating-free coating process, which has higher requirements for the surface quality of steel plates and stricter requirements for product roughness and corrugation. Therefore, it is imperative to develop outer panel products with high surface quality and excellent formability according to the use of customer parts.

[0003] In the prior art, CN115369314B - A bake-hardened hot-dip galvanized steel sheet with low corrugation and a method for manufacturing the same discloses a bake-hardened hot-dip galvanized steel sheet with low corrugation and anti-aging, the surface roughness Ra of which is in the range of 0.9-1.4μm, and the corrugation Wsa measured after 5% uniform deformation is less than 0.35μm. The core process point of the patent is to adopt high flatness (elongation of flattening treatment ≥1.2%), but no research is conducted on optimizing the whole process process to refine the grain to improve the corrugation of the galvanized automobile sheet substrate.

[0004] CN112538593B-A method for producing hot-dip galvanized IF steel sheet with controlled surface waviness discloses a method for producing hot-dip galvanized IF steel sheet with controlled surface waviness. By rationally designing the chemical composition of the steel sheet, adjusting the process parameters of hot rolling and annealing, and controlling the surface roughness of the polishing roller, etc., the surface texture of the hot-dip galvanized IF steel sheet after stamping is improved to meet the requirements of the 2C1B painting process. The corrugation of the original steel sheet produced by this patent is Wsa 1-5 <0.35μm, but the waviness value after forming is not disclosed. There is a possibility that the waviness after forming does not meet the standard requirements, and there is no description of the method or technical details for controlling the waviness of the coating.

[0005] Application No. CN110527921A discloses a method for controlling the surface morphology of hot-dip galvanized ultra-deep drawing steel for automobile panels. By controlling the production process, especially the process conditions of cold rolling and hot-dip galvanizing, the hot-dip galvanized ultra-deep drawing steel has good tensile properties and its surface roughness and corrugation can meet the requirements of automobile factories. The corrugation of the original steel plate produced by this method is Wsa 1-5 <0.35μm, but the waviness value after forming is not disclosed, there is a possibility that the waviness after forming does not meet the standard requirements, and this method does not study the influence of grain structure on the waviness of the finished product after deformation.

[0006] CN114438417B-Pure zinc-coated steel sheet with good anti-dezincification performance and surface quality and its production method and application discloses a production method of pure zinc-coated steel sheet with good anti-dezincification performance and surface quality. Through chemical composition and supporting process design, needle-shaped missed plating points with a diameter of 0.1 to 1.0 μm are avoided on the surface, and the bottom of the surface finishing pit is ensured to be smooth without mechanical damage. Even if the zinc layer falls off during stamping plastic deformation, it will not accumulate inside the mold and pollute the mold. The steel sheet produced by this method has high Si, Mn, and P components and belongs to high-strength IF steel sheet, and the corrugation is not studied. Summary of the invention

[0007] The purpose of the present invention is to overcome the problems of high corrugation of the original plate and high corrugation after forming in the prior art, and to provide a low-corrugation galvanized IF steel outer plate and a preparation method thereof. This solution solves the problem of excessive long waves in the 2C1B coating process without mid-coating due to excessive corrugation of the steel plate after stamping deformation, which can greatly improve the brightness of the steel plate after forming and coating, and is of great significance and practical value to improving the production efficiency of automobile companies.

[0008] In order to achieve the above-mentioned object, the present invention provides a low-corrugation galvanized IF steel outer plate on one hand, wherein the low-corrugation galvanized IF steel outer plate comprises the following chemical components in weight percentage: 0<C≤0.0035%, 0<Si≤0.03%, 0.08%≤Mn≤0.25%, 0<P≤0.02%, 0<S≤0.015%, 0.02%≤Al≤0.055%, 0.02%≤Ti≤0.075%, 0≤Nb≤0.035%, 0≤N≤0.005%, and the rest is Fe and unavoidable impurities;

[0009] The low-corrugation galvanized IF steel outer plate has a corrugation Wsa≤0.35 μm.

[0010] The present invention is based on the corrugation characteristic value Wsa of cold-rolled metal flat products in the German steel industry SEP 1941-2012 1-5 The waviness Wsa is detected by the enterprise standard formulated according to the measurement standard. The detection method is as follows: 1) Sample preparation: Use the Marciniak cup test to plastically deform the test specimen at a strain of 3% to 10%, generally at a strain of 5%; 2) Detection: Before measurement, the surface of the specimen should be wiped and degreased with industrial alcohol (the surface of the specimen must not have any contamination or mechanical defects (such as scratches)), and then use the waviness detection equipment to measure at least three times along the rolling direction in the middle position of the plane area of ​​the specimen, with an interval of about 15mm each time, and calculate the average value as the waviness Wsa of this test specimen.

[0011] The functions and content control reasons of the chemical components in the low-corrugation galvanized IF steel outer plate of the present invention are as follows:

[0012] C: When the C content is low, its formability and welding performance are better; a trace amount of solid solution carbon can enhance the grain boundary strength and improve the secondary processing brittleness. Too high a carbon content is not conducive to formability. Considering that the outer plate products have multiple grades from DDQ to SEDDQ, in the present invention, the C content is controlled within the above range.

[0013] Si: has a strong strengthening effect in steel, but Si easily forms oxides, which is not conducive to pickling and the surface is prone to form oxidation color after annealing, and also reduces the coating and plating properties of the steel plate. Therefore, the present invention adds a small amount of Si, and it is more appropriate to control its content within the above range.

[0014] Al: Al is a common deoxidizer in steel. If the Al content is too low, coarse Mn and Si oxides will increase, reducing the purity of the steel. If the Al content is too high, the crystallizer will be easily blocked, and aluminum oxide inclusions will be easily generated, which will damage the plasticity of the steel and increase the difficulty of smelting and casting. At the same time, AlN particles formed by combining with N can pin the grain boundaries and play a certain role in refining the grains. Therefore, the Al content in the present invention is controlled within the above range.

[0015] Ti: It is mainly used to fix free N and S atoms in the steel of the present invention. Too little Ti cannot completely fix N atoms, which is not conducive to improving aging properties. Too much Ti will increase manufacturing costs and lead to a high yield strength of the product, and will be oxidized during the annealing process to affect the wettability with zinc liquid. Therefore, it is more appropriate to control its content within the above range.

[0016] Nb: According to the product grade and use, two design ideas are adopted: single Ti or Ti+Nb composite component. Among them, the Ti+Nb composite component mainly utilizes Nb to combine with C atoms to generate NbC, which is dispersed and precipitated in the hot rolling coiling stage, and can be precipitated in large quantities with TiN precipitated in the finishing rolling stage as the nucleation particle, so that the nucleation rate of ferrite is greater than its growth rate, thereby achieving the purpose of refined and uniform ferrite grains. The Nb precipitates are finer and dispersed in the coiling process. These fine NbC particles can inhibit the development of grains in the steel plate in the same direction during the subsequent annealing process, and can play a role in improving the anisotropy of the steel plate. This is extremely important for complex parts that require uniform deformation rates in different directions, and it is difficult to achieve good anisotropy with a single Ti component, but excessive addition of Nb will increase costs, so its content is controlled within the above range.

[0017] P / S / N / Mn: S and Mn are a pair of interacting chemical elements. Mainly, Mn neutralizes S to form MnS to reduce hot brittleness. P is a residual impurity element that must be controlled at a low level. N causes the aging properties of steel to deteriorate and should also be controlled at a low level.

[0018] The metallographic structure of the low-corrugation galvanized IF steel outer plate of the present invention is ferrite, and the average grain size of the low-corrugation galvanized IF steel outer plate is 8.5-9.5.

[0019] Furthermore, the thickness of the low corrugation galvanized IF steel outer plate is 0.6-0.8 mm, and the elongation after fracture A 80 30~50%, work hardening rate n 90 ≥0.21, plastic strain ratio r 90 ≥2.3, roughness 0.6~1.2μm (here refers to the roughness of the upper and lower surfaces of the low-corrugation galvanized IF steel outer plate are both 0.6~1.2μm);

[0020] The low-corrugation galvanized IF steel outer plate has a yield strength of 130-180 MPa and a tensile strength of 275-320 MPa.

[0021] In a specific embodiment, the metallographic structure is detected by a metallographic microscope, and the yield strength, tensile strength and elongation after fracture A 80 It is measured in accordance with GB / T 228.1-2021: Tensile test of metallic materials Part 1: Test method at room temperature; plastic strain ratio r 90 The test is carried out in accordance with GB / T5027-2016: Determination of plastic strain ratio (r value) of metal sheets and strips; work hardening rate n 90 The test is carried out in accordance with "GB / T 5028-2008: Determination of tensile strain hardening index (n value) of metal sheets and strips"; the roughness is measured in accordance with "GB / T 2523-2022 Measurement method of surface roughness, peak number and waviness of cold-rolled metal sheets and strips"; the average grain size is measured in accordance with "GB / T 6394-2017 Determination method of average grain size of metals".

[0022] A second aspect of the present invention provides a method for preparing the low-corrugation galvanized IF steel outer plate, the method comprising the following steps:

[0023] (1) heating and dephosphorizing the slab, then hot rolling, laminar cooling after the hot rolling, and then coiling and air cooling to obtain a hot coil; wherein the hot rolling final rolling temperature is 910-930° C., and the coiling temperature is 600-700° C.;

[0024] (2) pickling and cold rolling the hot coil obtained in step (1) to obtain a hard rolled coil;

[0025] (3) continuously annealing the hard rolled coil obtained in step (2), cooling after the continuous annealing, then hot-dip galvanizing, and finally skin-passing to obtain a low-corrugation galvanized IF steel outer plate;

[0026] Wherein, the heating temperature of the continuous annealing is 780-810°C;

[0027] The hot-dip galvanizing conditions include: a production line speed of 100 to 120 m / min, an air knife spacing of 7.5 to 9.5 mm;

[0028] The skin-passing conditions include: skin-passing elongation of 0.8-1.2%, skin-passing rolling force of 250-400t, and roller roughness of ≤1.8μm.

[0029] In step (1), the method for preparing the slab comprises: subjecting molten iron to pretreatment, converter smelting and RH vacuum treatment in sequence to obtain molten steel, and continuously casting the molten steel to obtain the slab.

[0030] The above-mentioned pretreatment of molten iron is a conventional operation in the art, which specifically includes desulfurization, dephosphorization and desiliconization, and the purpose is to remove impurities in the molten iron.

[0031] The chemical composition content of the molten steel obtained in the present invention is consistent with that of the low-corrugation galvanized IF steel outer plate finally obtained. Under the action of the crystallizer, the molten steel is formed and rapidly solidified and crystallized to form a slab.

[0032] In step (1), the slab obtained by the present invention needs to be heated before hot rolling, and the heating temperature is controlled to be 1180-1220°C. The lower heating temperature is adopted to retain the coarse and undissolved C and N compounds of Ti, and to form coarse precipitates in advance during the subsequent hot rolling process. These coarse precipitates serve as the precipitation particles of Nb C compounds in the subsequent coiling process to refine the grains. The hot rolling adopts a final rolling temperature of 910-930°C in order to fully utilize the deformation induction effect to obtain a large number of uniform and fine original austenite grains by rolling at a temperature slightly higher than the austenite critical ferrite transformation temperature of 880°C, while avoiding the rolling temperature falling into the two-phase temperature range to cause uneven grain size and mixed crystal structure.

[0033] Further in step (1), the hot rolling includes 3 to 9 passes of rough rolling and 3 to 9 passes of finish rolling, and the start temperature of the finish rolling is 950 to 1100°C.

[0034] In a preferred embodiment, the coiling temperature in step (1) is controlled to be 600-700°C in order to fully identify the application, set a suitable coiling temperature according to the application, and further improve the uniformity of the structure by utilizing the fine grain strengthening effect of NbC at a slightly lower coiling temperature while controlling the hot coil performance.

[0035] In a specific embodiment, the thickness of the hot coil obtained in step (1) is 3 to 4.5 mm.

[0036] In step (2), the hot coil obtained in step (1) is subjected to turbulent pickling and then cold rolled by 5 stands, and the total reduction rate of the cold rolling is controlled to be 78-84%. The thickness of the hard rolled coil obtained is 0.575-0.825 mm. In order to fully ensure that there is sufficient deformation energy storage in the annealing process and allow the favorable texture to fully develop, for the typical finished product thickness of deep-drawn steel for outer covering parts of 0.6-0.8 mm, the total reduction rate of cold rolling is not less than 78%. Considering the rolling mill capacity, the total reduction rate of cold rolling does not exceed 84%, so it is considered to adopt a total reduction rate of cold rolling of 78-84%.

[0037] In a specific implementation of step (3), the hard rolled coil obtained in step (2) needs to be cleaned and degreased before continuous annealing.

[0038] Wherein in step (3), the soaking temperature of the continuous annealing is 780-810°C; after the continuous annealing is completed, the hard rolled coil after the continuous annealing is cooled to 450-490°C in a mixed gas of H2 and N2, and then enters the zinc pot for hot-dip galvanizing through the furnace nose; wherein the content of H2 in the mixed gas is 3-10 volume %.

[0039] In step (3) of the present invention, the hot-dip galvanizing conditions also include: the zinc pot temperature is 450-465° C., and the air knife pressure is 400-600 mbar.

[0040] Since hot-dip galvanizing adopts a fast production speed (100-120m / min) + a small air knife spacing (7.5-9.5mm), and further adopts a small air knife pressure (400-600mbar), it can reduce the uneven thickness fluctuation caused by the zinc layer gradually decreasing in the longitudinal fluidity of the strip due to the slow cooling rate and the lack of time for the zinc liquid to solidify quickly during the zinc pot solidification process.

[0041] Furthermore, no slag removal is performed during the hot-dip galvanizing process to ensure that the zinc pot liquid level fluctuation is within the range of ±1mm, thereby reducing the amount of zinc slag and zinc ash on the surface (if slag removal is performed, and the liquid level fluctuation exceeds the range of ±1mm during slag removal, the zinc slag will be disturbed and adsorbed on the surface of the high-speed moving strip, affecting the surface quality).

[0042] One of the important functions of the finishing operation in step (3) of the present invention is to give the steel plate surface a certain degree of roughness. The finishing roller grinding method adopted in the present invention adopts the mature and economical EDT process. Small roughness EDT rollers are used, with roller roughness ≤1.8μm, further 1.4μm~1.8μm, and the skin-clearing elongation is controlled at 0.8~1.2%, because too high skin-clearing elongation will lead to deterioration of forming performance, increased corrugation, roughness, stretch marks, orange peel and other defects on the surface after stamping, while too low skin-clearing elongation will lead to heavy surface moire and defects such as incompatible performance. Therefore, it is more appropriate to control the skin-clearing elongation at 0.8~1.2%; and large rolling force is used for production, and the skin-clearing rolling force (i.e., the total skin-clearing rolling force in the plate width direction) is 250~400t (250~400 tons), which increases the depth and density of skin-clearing pits and roughness troughs on the steel plate surface, ensures the plate shape and mechanical properties, enhances the ability of the steel plate surface to store stamping lubricating oil, and at the same time can improve the plate shape, improve the plate surface quality, and reduce stamping defects caused by surface defects of the steel plate itself (black spots, bright spots, dezincification powder, etc.).

[0043] Compared with the prior art, the present invention has the following advantages:

[0044] (1) Using appropriate final rolling temperature (910-930°C) and appropriate coiling temperature (600-700°C, different coiling temperatures are used for different purposes) is conducive to grain refinement, improving deep drawing performance and reducing substrate waviness and waviness after 5% deformation;

[0045] (2) Hot-dip galvanizing uses a faster production speed (100-120 m / min) + a smaller air knife spacing (7.5-9.5 mm) to reduce the gravity flow of zinc liquid along the strip during the solidification process of the zinc pot, reduce the unevenness of the zinc layer and thickness fluctuations caused by this, improve the uniformity and surface quality of the coating, and reduce the corrugation of the zinc layer; at the same time, a lower heating temperature (780-810 ° C) is matched during continuous annealing to prevent abnormal grain growth and affect the stamping effect;

[0046] (3) Use low-roughness rollers (roller roughness ≤ 1.8 μm) for skin-pass rolling to reduce the waviness increment before and after deformation, that is, reduce the waviness after 5% deformation; the skin-pass elongation is controlled at 0.8-1.2% to improve the surface quality;

[0047] (4) The finishing process uses a large rolling force (250-400 tons) to increase the depth and density of the finishing pits and roughness troughs on the steel plate surface, enhance the ability of the steel plate surface to store stamping lubricating oil, and at the same time improve the plate shape and surface quality, and reduce stamping defects (black spots, bright spots, dezincification powder, etc.) caused by surface defects of the steel plate itself. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 This is a metallographic structure picture of the low-corrugation galvanized IF steel outer plate of Example 1;

[0049] Figure 2 This is a surface picture of the low-corrugation galvanized IF steel outer plate of Example 1 after 5% strain plastic deformation. DETAILED DESCRIPTION

[0050] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.

[0051] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0052] Example 1

[0053] (1) pre-treating molten iron (desulfurization, dephosphorization and desiliconization treatment), converter smelting and RH vacuum treatment in sequence to obtain molten steel, continuously casting the molten steel to obtain slabs, heating the slabs at a temperature of 1201° C., dephosphorizing and hot rolling, the hot rolling including 6 passes of rough rolling and 7 passes of finishing rolling, the start rolling temperature of finishing rolling is 1033° C., the final rolling temperature of hot rolling is 912° C., laminar cooling is performed after the hot rolling is completed, followed by coiling and air cooling to obtain hot coils, the thickness of the hot coils is 3.867 mm; wherein the coiling temperature is 650° C.;

[0054] (2) subjecting the hot coil obtained in step (1) to turbulent pickling and then to 5-stand cold rolling, wherein the total cold rolling reduction ratio is 83.66%, to obtain a hard rolled coil, wherein the thickness of the hard rolled coil is 0.632 mm;

[0055] (3) The hard rolled coil obtained in step (2) is cleaned and degreased, and then continuously annealed, the heating temperature of the continuous annealing is 803° C., the soaking temperature of the continuous annealing is 805° C., and after the continuous annealing is completed, the hard rolled coil after continuous annealing is cooled to 476° C. in a mixed gas of H2 and N2, the content of H2 in the mixed gas is 5% by volume, and the content of N2 is 95% by volume, and then enters the zinc pot for hot-dip galvanizing through the furnace nose, and the conditions of hot-dip galvanizing include: the production line speed is 100 m / s / min, air knife spacing is 9.5mm, zinc pot temperature is 460℃, air knife pressure is 540mbar, no slag removal is performed during the hot-dip galvanizing process, and the zinc pot liquid level fluctuation is ensured to be within the range of ±1mm. Finally, skin pass is performed. The skin pass conditions include: skin pass elongation is 1.1%, skin pass rolling force is 305t, and roller roughness is 1.8μm. Low-corrugation galvanized IF steel outer plate is obtained, and the finished product thickness of the obtained low-corrugation galvanized IF steel outer plate is 0.65mm;

[0056] The low-corrugation galvanized IF steel outer plate obtained in this embodiment consists of the following chemical components in weight percentage: C: 0.0020%, Si: 0.0048%, Mn: 0.1193%, P: 0.0132%, S: 0.0038%, Al: 0.0399%, Ti: 0.0396%, Nb: 0.0129%, N: 0.0020%, and the rest is Fe and unavoidable impurities.

[0057] Examples 2-6, Comparative Examples 1-6

[0058] Low corrugation galvanized IF steel outer plates were prepared according to the method of Example 1, and the different process conditions are shown in Tables 1 and 2 (the process conditions not mentioned in Tables 1 and 2 are consistent with Example 1, and the thickness of the obtained low corrugation galvanized IF steel outer plates is shown in Table 1). The chemical composition content of the obtained low corrugation galvanized IF steel outer plates is shown in Table 3, and the remainder not shown in Table 3 is Fe and unavoidable impurities.

[0059] Table 1 Hot-rolled, cold-rolled processes and finished thickness of low-corrugation galvanized IF steel outer plates

[0060]

[0061] Table 2 Continuous annealing, hot dip galvanizing and skin finishing process

[0062]

[0063]

[0064] Table 3 Chemical composition of low corrugation galvanized IF steel outer plate (weight percentage)

[0065] serial number C(%) Si(%) Mn(%) P(%) S(%) Al(%) Ti(%) Nb(%) N(%) Example 1 0.0020 0.0048 0.1193 0.0132 0.0038 0.0399 0.0396 0.0129 0.0020 Example 2 0.0016 0.0040 0.1100 0.0092 0.0076 0.0400 0.0390 0.0199 0.0019 Example 3 0.0016 0.0024 0.1070 0.0149 0.0111 0.0460 0.0678 0.0009 0.0022 Example 4 0.0018 0.0039 0.1104 0.0112 0.0048 0.0485 0.0397 0.0206 0.0020 Example 5 0.0013 0.0027 0.1098 0.0106 0.0046 0.0332 0.0395 0.0191 0.0016 Example 6 0.0016 0.0025 0.0995 0.0105 0.0058 0.0380 0.0538 0.0053 0.0021 Comparative Example 1 0.0009 0.0041 0.1109 0.0114 0.0052 0.0405 0.0394 0.0183 0.0022 Comparative Example 2 0.0010 0.0069 0.1172 0.0134 0.0048 0.0440 0.0430 0.0194 0.0012 Comparative Example 3 0.0010 0.0045 0.1107 0.0114 0.0046 0.0446 0.0405 0.0209 0.0017 Comparative Example 4 0.0014 0.0051 0.1139 0.0134 0.0050 0.0457 0.0402 0.0179 0.0025 Comparative Example 5 0.0015 0.0017 0.1103 0.0103 0.0082 0.0426 0.0588 0.0007 0.0018 Comparative Example 6 0.0014 0.0021 0.1106 0.0164 0.0101 0.0422 0.0602 0.0004 0.0020

[0066] Test Example 1

[0067] The metallographic structure and grain size of the low-corrugation galvanized IF steel outer plate of Example 1 were detected. The metallographic structure was detected by a metallographic microscope. The grain size grade and the average grain size were determined according to the "GB / T 6394-2017 Method for Determining the Average Grain Size of Metals". After testing, the grain size grade was 9 and the average grain size was 8.5-9.5. The metallographic structure picture is as shown in Figure 1 As shown, according to Figure 1 It can be seen that the finished product produced by the scheme of the present invention has fine and uniform grains, and the matrix metallographic structure is a single ferrite; the detection results of other embodiments are similar to those of Example 1, the metallographic structure is a single ferrite, the grains are fine and uniform, the grain size level is 9, and the average grain size is 8.5-9.5.

[0068] Test Example 2

[0069] The corrugation Wsa, elongation after fracture A80, and work hardening rate n of the low corrugation galvanized IF steel outer plates obtained in Examples 1-6 and Comparative Examples 1-6 were respectively tested. 90 , plastic strain ratio R 90 , roughness (roughness of the upper and lower surfaces), yield strength and tensile strength, the results are shown in Table 4;

[0070] Wsa detection method: 1) Sample preparation: Marciniak cup test is used to plastically deform the test sample according to 5% strain; 2) Detection: Before measurement, the sample surface should be wiped and degreased with industrial alcohol (the sample surface must not have any pollution and mechanical defects (such as scratches)), and then the waviness detection equipment is used to measure at least three times along the rolling direction at the middle position of the sample plane area, with an interval of about 15mm each time, and the average value is calculated as the final waviness Wsa result; the photo of the low-waviness galvanized IF steel outer plate of Example 1 after 5% strain plastic deformation is shown in the figure Figure 2 As shown;

[0071] Yield strength, tensile strength and elongation after fracture A 80 :Measured in accordance with GB / T 228.1-2021: Tensile test of metallic materials Part 1: Room temperature test method;

[0072] Plastic strain ratio r 90 :Testing is carried out in accordance with GB / T 5027-2016: Determination of plastic strain ratio (r value) of metal sheets and strips;

[0073] Work hardening rate n 90:Testing is carried out in accordance with GB / T 5028-2008: Determination of tensile strain hardening index (n value) of metal sheets and strips;

[0074] Roughness: Determined in accordance with GB / T 2523-2022 Measurement method for surface roughness, peak number and waviness of cold-rolled metal sheets and strips.

[0075] Table 4

[0076]

[0077] It can be seen from the results in Table 4 that the products produced by the scheme of the present invention have good mechanical properties and roughness. 90 and n 90 Relatively better, with excellent forming performance, and after 5% strain plastic deformation, the corrugation Wsa is less than or equal to 0.30μm, the corrugation Wsa is low, and it has good low corrugation characteristics after forming; and according to Figure 2 The results show that the low-corrugation galvanized IF steel outer plate obtained in Example 1 has no obvious tensile streaks or other surface defects that affect the appearance and corrugation results after 5% strain plastic deformation. The surface pictures of the low-corrugation galvanized IF steel outer plates in other embodiments after 5% strain plastic deformation are the same as those in Example 1, and all have no obvious tensile streaks or other surface defects that affect the appearance and corrugation results, indicating that the surface quality of the low-corrugation galvanized IF steel outer plate obtained by the present invention is high.

[0078] It should be understood that parts not elaborated in detail in this specification belong to the prior art.

[0079] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A low corrugation galvanized IF steel outer plate, characterized in that: The low-corrugation galvanized IF steel outer plate comprises the following chemical compositions in weight percentage: 0<C≤0.0035%, 0<Si≤0.03%, 0.08%≤Mn≤0.25%, 0<P≤0.02%, 0<S≤0.015%, 0.02%≤Al≤0.055%, 0.02%≤Ti≤0.075%, 0≤Nb≤0.035%, 0≤N≤0.005%, and the remainder is Fe and unavoidable impurities; The low-corrugation galvanized IF steel outer plate has a corrugation Wsa≤0.35 μm.

2. The low-corrugation galvanized IF steel outer plate according to claim 1, characterized in that: The metallographic structure of the low-corrugation galvanized IF steel outer plate is ferrite, and the average grain size of the low-corrugation galvanized IF steel outer plate is 8.5-9.

5.

3. The low-corrugation galvanized IF steel outer plate according to claim 1 or 2, characterized in that: The thickness of the low corrugation galvanized IF steel outer plate is 0.6-0.8 mm, and the elongation after fracture is A 80 30~50%, work hardening rate n 90 ≥0.21, plastic strain ratio r 90 ≥2.3, roughness 0.6~1.2μm; The low-corrugation galvanized IF steel outer plate has a yield strength of 130-180 MPa and a tensile strength of 275-320 MPa.

4. The method for preparing the low-corrugation galvanized IF steel outer plate according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: (1) heating and dephosphorizing the slab, then hot rolling, laminar cooling after the hot rolling, and then coiling and air cooling to obtain a hot coil; wherein the hot rolling final rolling temperature is 910-930° C., and the coiling temperature is 600-700° C.; (2) pickling and cold rolling the hot coil obtained in step (1) to obtain a hard rolled coil; (3) continuously annealing the hard rolled coil obtained in step (2), cooling after the continuous annealing, then hot-dip galvanizing, and finally skin-passing to obtain a low-corrugation galvanized IF steel outer plate; Wherein, the heating temperature of the continuous annealing is 780-810°C; The hot-dip galvanizing conditions include: a production line speed of 100 to 120 m / min, an air knife spacing of 7.5 to 9.5 mm; The skin-passing conditions include: skin-passing elongation of 0.8-1.2%, skin-passing rolling force of 250-400t, and roller roughness of ≤1.8μm.

5. The preparation method according to claim 4, characterized in that: In step (1), the method for preparing the slab comprises: subjecting molten iron to pretreatment, converter smelting and RH vacuum treatment in sequence to obtain molten steel, and continuously casting the molten steel to obtain the slab.

6. The preparation method according to claim 4 or 5, characterized in that: In step (1), the heating temperature is 1180-1220°C; The hot rolling includes 3 to 9 passes of rough rolling and 3 to 9 passes of finishing rolling, and the finishing rolling start temperature is 950 to 1100° C. The thickness of the hot coil is 3 to 4.5 mm.

7. The preparation method according to claim 4, characterized in that: In step (2), the total reduction ratio of the cold rolling is 78-84%, and the thickness of the hard rolled coil is 0.575-0.825 mm.

8. The preparation method according to claim 4, characterized in that: In step (3), the hard rolled coil obtained in step (2) is cleaned and degreased before continuous annealing.

9. The preparation method according to claim 4 or 8, characterized in that: In step (3), the continuous annealing is performed at a soaking temperature of 780 to 810°C; After the continuous annealing is completed, the hard rolled coil after the continuous annealing is cooled to 450-490° C. in a mixed gas of H 2 and N 2 , wherein the content of H 2 in the mixed gas is 3-10 volume %.

10. The preparation method according to claim 4, characterized in that: In step (3), the hot-dip galvanizing conditions also include: the zinc pot temperature is 450-465° C., and the air knife pressure is 400-600 mbar.

Citation Information

Patent Citations

  • Method for controlling surface appearance of hot-dip galvanized ultra-deep drawing steel for automobile panel

    CN110527921A

  • A method for producing hot-dip galvanized IF steel sheets with controlled surface waviness

    CN112538593B